Expression of transient receptor potential vanilloid (TRPV) channels in different passages of articular chondrocytes - Hdud, Ismail M.; El-Shafei, Abdelrafea A.; Loughna, Paul; Barrett-Jolley, Richard; Mobasheri, Ali (MDPI, 2012)
Ion channels play important roles in chondrocyte mechanotransduction. The transient receptor potential vanilloid (TRPV) subfamily of ion channels consists of six members. TRPV1-4 are temperature sensitive calcium-permeable, relatively non-selective cation channels whereas TRPV5 and TRPV6 show high selectivity for calcium over other cations. In this study we investigated the effect of time in culture and passage number on the expression of TRPV4, TRPV5 and TRPV6 in articular chondrocytes isolated from equine metacarpophalangeal joints. Polyclonal antibodies raised against TRPV4, TRPV5 and TRPV6 were used to compare the expression of these channels in lysates from first expansion chondrocytes (P0) and cells from passages 1–3 (P1, P2 and P3) by western blotting. TRPV4, TRPV5 and TRPV6 were expressed in all passages examined. Immunohistochemistry and immunofluorescence confirmed the presence of these channels in sections of formalin fixed articular cartilage and monolayer cultures of methanol fixed P2 chondrocytes. TRPV5 and TRPV6 were upregulated with time and passage in culture suggesting that a shift in the phenotype of the cells in monolayer culture alters the expression of these channels. In conclusion, several TRPV channels are likely to be involved in calcium signaling and homeostasis in chondrocytes.